Phase, size and shape transformation by fungal biotransformation of bulk TiO2 - Khan, Shadab Ali; Ahmad, Absar (Chemical Engineering Journal, 2013)
Nanosynthesis is an ever expanding frontier in recent years in view of its implications to many future technologies covering diverse fields. Considerable progress has been made realizing high quality synthesis of elemental nanomaterials as well as compounds as chemical, biological and physical routes. The issue of technologically viable large scale synthesis still continues to be a challenge. Here we demonstrate a novel environmentally friendly top down approach to nanosynthesis which exploits the strength and peculiarities of fungus based bioleaching in extracting radicals from compounds and then providing them with a reactive as well as capping environment. Thus protein capped nanoparticles of TiO2 (5-28 nm, circular and brookite phase) are formed directly from micron size (150-250 nm, disc shape, anatase phase) powder by exposing them to a medium of fungus Humicola sp. at just 50 degrees C. The fungus Humicola sp. is not only useful for the synthesis of nanoparticles but also for the transformation of shape, phase and size of TiO2. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Anatase; Biotransformation; Brookite; humicola sp; TiO2